Association of leisure-time aerobic physical activity time with apparent treatment-resistant hypertension: a study based on NHANES database - Huang, Wanling; Lai, Dongqin; Zeng, Meie; Chen, Bin; Ye, Shuifen; Li, Fenjing; Huang, Chunmei (Biology of Sport, 2025)
Using information from the National Health and Nutrition Examination Survey (NHANES) database, this study intends to investigate the connection between apparent treatment resistant hypertension (aTRH) and leisure-time aerobic physical activity (LTAPA) time. A cross-sectional analysis was conducted on the NHANES data from 2007 to 2018.LTAPA time was used as the independent variable, and aTRH was used as the dependent variable. Participants’ baseline characteristics were collected and analyzed based on whether they had aTRH. A weighted regression model was used to analyze association of LTAPA time with aTRH, and a stratified analysis was conducted. In addition, the relationship between LTAPA and the risk of all-cause mortality in patients with aTRH was assessed and survival curves were plotted. 6,705 hypertensive patients were included, with 6,292 in non-aTRH group and 413 in aTRH group. Baseline results presented significant differences in age, race, povertyto income ratio (PIR), body mass index (BMI), number of cases of diabetes mellitus, and estimated glomerular filtration rate (eGFR) values between two groups ( p < 0.05). Weekly LTAPA time was significantly lower in aTRH group than in non-aTRH patients (76.15 vs. 103.16, p = 0.016). Weighted logistic regression modeling showed that an increase in LTAPA time was associated with a reduced risk of developing aTRH (OR = 0.939, 95%CI [0.884,0.999], p = 0.045), especially among female patients who did not drink alcohol. Weighted Cox regression analysis showed a significant negative association between LTAPA time and risk of all-cause mortality (OR = 0.900, 95%CI [0.831,0.976], p = 0.010). Kaplan-Meier survival analysis also showed that an increase in LTAPA time significantly prolonged the survival time of aTRH patients (Log-rank p < 0.001). Increasing LTAPA time among American adults was associated with the reduced incidence and mortality of aTRH, especially in women who do not drink alcohol. In the future, gender-specific exercise strategies could be considered, along with drug therapy and other non-pharmacological interventions, to develop targeted treatment strategies for hypertensive patients to reduce the incidence and mortality of aTRH.